Analisis komparatif kandungan metabolit pada daun mutan tanaman Torbangun (Plectranthus amboinicus (Lour.) Spreng.): Analisis komparatif kandungan metabolit pada daun mutan tanaman Torbangun (Plectranthus amboinicus (Lour.) Spreng.) - Syarifah Iis Aisyah; Henny Rusmiyati; Dewi Sukma; Rizal Damanik; Waras Nurcholis (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2020)
Torbangun (Plectranthus amboinicus) is a medicinal plant belonging to the Lamiaceae family. In Batak society, the torbangun leaves are consumed to increase breast milk production. The phytochemical variability can be improved by gamma-ray irradiation for plant breeding programs. In this work, a non-targeted metabolomics method was followed to evaluate the compounds profile of irradiated mutant and wild-type on leaves of P. amboinicus. GC-MS analyses evaluated the mutant putative (derived from gamma-ray irradiation) and wild-type plantlets. The resulting of GC-MS data were analyzed with chemometric analysis using hierarchical cluster analysis (HCA). The chemical diversity was showed in mutant and wild-type P. amboinicus. The major metabolite in plantlet wild-type were hydroxymethylfurfural (35.15%), brevifolin (7.69%), 3-Dihydro-3,5-Dihydroxy-6-Methyl-4H-Pyran-4-one (DDMP) (13.13%), stigmasterol (6.51%) and ferruginol (8.63%). However, the compound of DDMP (19.57%), neophytadiene (8.47%), linolenic acid (9.10%), ferruginol (7.61%), stigmasterol (14.14%) and gamma-sitosterol (7.08%) were identified in mutant plantlet. HCA showed diversity between wild-type and mutant plantlets, which highest content of DDMP and stigmasterol and lowest of hydroxymethylfurfural of mutant plantlet.